Impact of Body Esteem on Antenatal Depression Among Pregnant Women of South Punjab-Moderating Role of Social Support - Saleem, Mohammad; Hashmi, Hijab Fatima; Durrani, Areeha Khan; Manzoor, Zubair (Journal of Pakistan Psychiatric Society, 2019)
ABSTRACT